Human factors considerations in the selection of a uniform protected/permitted left-turn signal display - Noyce, David A. (My University, 1999)
This paper provides an in-depth review of the current understanding in the human factors aspects of traffic signal operations, focused primarily on protected/permitted left-turn (PPLT) control and the corresponding PPLT signal display. PPLT signal phasing provides an exclusive phase for left turns, as well as a permissive phase during which left turns can be made if gaps in opposing through traffic allow, all within the same signal cycle. The first section of the paper provides an overview of general concepts related to human factors aspects of traffic signal displays including the visual search process, driver perception and reaction, driver recognition and comprehension, driver expectancy, and signal display complexity. The next section provides a detailed overview of color vision and how humans observe the red, yellow, and green traffic signal indications. The third section discusses older driver issues by briefly looking at visual and cognitive changes associated with the human aging process. Finally, several comments related specifically to the selection of a uniform PPLT signal display are presented.
21 p. ; Paper prepared for Transportation Frontiers for the Next Millennium: 69th Annual Meeting of the Institute of Transportation Engineers, Las Vegas, Nevada, August 1-4, 1999.
Keywords: Human factors; Visual perception; Color vision; Exclusive permissive phasing; Left turn phase; Traffic signal phases; Cognition; Aging (Biology); Aged drivers